Joaquim Pedro de Andrade: primeiros tempos - Brincalepe Campo, Mônica (Imagofagia, 2021)
Sobre Araújo, Luciana Corrêa de. Joaquim Pedro de Andrade: primeiros tempos. São Paulo: Alameda Editorial, 2013, 294 pp., ISBN: 978-85-7939-154-5. Palabras clave: reseña, Araújo, Luciana Corrêa de, Pedro de Andrade: primeiros tempos.